Effectiveness of the “Sweet and healthy life” program in the knowledge and practices of self-care in adult patients with Diabetes Mellitus at the Primary Care Center III - Huaycán, Lima, 2017 - Lazo Villalta, Astrid Eloisa (2018)
Objective: To determine the effectiveness of the program “Sweet and healthy life” in the knowledge and practices of self-care in adult patients with Diabetes Mellitus at the Primary Care Center III - Huaycán. Materials and Methods: Quasi experimental design, longitudinal section. The sample consisted of two groups, 27 in the control group and 27 in the experimental group, selected by non-probabilistic sampling, the program lasted 2 months and a pre and post test was applied. The instruments used for data collection were adapted by the researchers, a questionnaire was used for the level of knowledge validated with a KR-20 of 0.80 and to measure the practices it was an observation guide that reached a KR20 of 0.81. Results: It shows that the educational program was effective in the knowledge and practices of self -care in adult patients with Diabetes Mellitus with a p-value of 0.00, through the non-parametric Wilcoxon test. Conclusions: It is concluded that the intervention program is effective in the study variables.